4-H Recycling Adventures - Craig Miller; Joy Cantrell Jordan (EDIS, 2002)
Produced by the Department of 4-H and Other Youth Programs, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences. University of Florida, April 1992. Reviewed June 2002.